RISK OF RETURNING DEPOSITO INVESTMENT RESULTS - Djoko Sigit Gunanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
The purpose of this study is to understand the risk and return on investment of mudharabah deposits in Islamic banks using the Value at Risk (VaR) approach. The objects in this study are quarterly financial reports of Bank Syariah Mandiri, Bank BRI Syariah, and Bank Muamalat for three years, 2015-2017. VaR analysis results show that the average investment risk of mudharabah deposits for 3 years at Bank Syariah Mandiri was in 2015 amounted to 6.61% and net return of -0.53%, in 2016 the risk of 0.14% and net return of 3.21 %, in 2017 the risk is 0.17% and the net return is 0.32%. BRI Syariah Bank in 2015 was 0.08% and net return was 4.28%, in 2016 the risk was 0.07% and the net return was 3.77%, in 2017 the risk was 0.08% and the net return was 42.81% . and Bank Muamalat was in 2015 amounted to 0.63% and a net return of 0.04%, in 2016 a risk of 0.40% and a net return of 0.08%, in 2017 a risk of 0.14% and a net return of 0.26% . In addition there are differences in the level of risk and net return on Bank Syariah Mandiri, Bank BRI Syariah, and Bank Muamalat with a significant probability (p-value) for a risk level of 0.005 and a net return of 0.045. From the level of risk and net return for three years, BRI Syariah Bank is a bank that has a prospective value. Keywords: VaR, Risk, Return, Mudharabah Deposit